Experimental investigation of overall heat transfer coefficients for adsorption bed under adsorption-desorption operating conditions - Koh, Gordon Yong Feng (Nanyang Technological University, 2022)
The need to supply energy for human civilisation are constantly at odds with climate change. The major demands of energy are lighting, heating, cooling, water supply and many others. To meet these demands, energy is traditional sourced from combustion of fossil fuels in power stations. However, fossil fuel combustion leads to the production of excess carbon dioxide and other pollutants. Carbon dioxides create large amounts of greenhouse gasses and traps heat within the earth atmosphere. This trapped heat leads to melting of polar ice caps, raising the sea level and cause flooding. The effects of the pollutants are the contribution to respiratory diseases. In addition to the many detrimental effects of burning fossil fuels, the rate of which fossil fuels are burned are not sustainable. Oil is expected to be depleted by the year 2052, while coal and gas by the year 2060. To reduce the reliance of fossil fuels, many alternative forms of energy generation have developed such as wind, solar, water and nuclear. However, these alternative forms of energy are insufficient to support the large energy demand hence methods to reduce energy consumption should be explored. Adsorption heat exchanger is among the many ways to reduce energy consumption. Adsorption heat exchangers can make use of low temperature heat waste to regenerate energy for heating and cooling applications. The performance of adsorption heat exchanger is largely dependent on the adsorbent materials, the working fluid, and the efficiency of adsorption beds. Adsorption beds are typically made from a helical tube heat exchanger housing adsorbent material. The characteristics of adsorption of the adsorbent-adsorbate working pair is necessary to be ascertained for the development of adsorption heat exchanger. Previous experiments have been performed on working pair such as silica gel with methanol or activated carbon with R134a. However extensive experiment has not been conducted with water vapour as the adsorbate with other adsorbent materials. Thus, the objective of this study is to determine the adsorption characteristic of adsorbent-adsorbate working pair of silica gel-water vapour as well as activated carbon-water vapour. The adsorption characteristic such as heat transfer coefficient (U-value), coefficient of performance (COP) as well as the specific cooling capacity (SCC) is determined using Log Mean Temperature Difference (LMTD) method and compared. The hot water temperature is varied between the range of 45℃ to 65℃ in an increment of 5℃. The cooling water temperature is varied between 15℃ to 35℃ in an increment of 5℃. The evaporator temperature and condenser temperature are fixed at 15℃ and 30℃ respectively. The switch time and operation time is 50s and 700s respectively. The results showed that typically as the temperature of hot water increases and temperature of cooling water decreases, the heat transfer coefficient with respect to the silica gel and activated carbon adsorption bed increases. However, after exceeding the ideal parameter, the heat transfer coefficient decreases. The typical range of heat transfer coefficient of silica gel and activated carbon adsorbate is found to be in the range of 130 – 210 W/m2K and 70 – 83 W/m2K respectively. The result also shows that although the silica gel bed has a better heat transfer coefficient, activated carbon have generally better COP and SCC compared to that of silica gel. With activated carbon having a COP of 0.4 – 0.5 and SCC of 1.0 – 1.8, while silica gel has a COP of 0.0 – 0.55 and SCC of 0.2 – 0.9.